EFFECTIVENESS OF CRIMINAL SANCTIONS IN CUSTOMS CRIMINAL ACTS IN THE FIELD OF EXCISE IN TERMS OF THE THEORY OF CRIMINAL LAW (Analysis of the Application of Criminal Sanctions for the Printing of Fake Excise Stamps at the Jakarta Customs and Excise Office) - SUTEJO, GATOT HARIYO (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
Law enforcement against counterfeiting cigarette tax band cannot be performed optimally due to factors that affect law enforcement itself. Law enforcement is required because of a violation of the customs excise lately is high enough, one of which counterfeit cigarette tax band conducted by firms to lower middle cigarette manufacturers. As a result of counterfeiting cigarette excise stamps, the potential losses to the state becomes large enough, within a year nearly one trillion. In addition to the state suffered a loss, smoking can also cause heart and good health to the user as active smokers as well as for passive smokers. Thus, the enactment of Law No. 11 of 1995 on Excise as subsequently amended by Act No. 39 of 2007, violations against counterfeiting cigarette excise stamps can be minimized by applying severe criminal system so that a deterrent effect. The issue is whether the punishment of a criminal offense customs have been effective if it is linked with the provisions of Article 50 through Article 62 of Law No. 11 of 1995 as amended by Act No. 39 of 2007 on Excise impose criminal sanctions most eight-year high in the excise criminal offense when the amount of losses the country billions of rupiah and whether criminal sanctions could have a deterrent effect against criminal excise? And how the solution so that punishment of a criminal offense can be effective excise? This study uses normative juridical approach. Research results that the provisions of criminal law governing the punishment of the crime of criminal customs there are weaknesses that the threat of criminal penalties were small or too light. Whereas the purpose of sentencing in the criminal law policy of modern Indonesia has changed from the purpose of punishment as revenge towards punishment with prevention purposes for the penalty should be increased.